2004
DOI: 10.1159/000079524
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Receptor Alleles, Bone Mineral Density and Turnover in Postmenopausal Osteoporotic and Healthy Women

Abstract: Objective: Vitamin D receptor (VDR) gene polymorphisms and bone metabolic markers were investigated as potential genetic markers for osteoporosis in postmenopausal Turkish women. The relationship between their VDR gene polymorphisms and bone states was determined. Materials and Methods: Restriction fragment length polymorphisms at the VDR gene locus (i.e., for BsmI, ApaI, and TaqI) was investigated in 75 postmenopausal osteoporotic (53.16 ± 1.31 years) and 66 healthy (52.62 ± 1.69 years) Turkish women and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 27 publications
0
21
1
1
Order By: Relevance
“…Although this initial finding has been partially withdrawn, in the following years, a large number of studies investigated the potential associations of VDR polymorphisms with BMD in different ethnic populations [4][5][6][7][8][9][10], as well as with other parameters such as bone loss [11,12], fractures [11,13,14] and bone turnover [14][15][16]. However, these studies have provided controversial and inconclusive results due to differences in sample size, ethnic background and age group [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Although this initial finding has been partially withdrawn, in the following years, a large number of studies investigated the potential associations of VDR polymorphisms with BMD in different ethnic populations [4][5][6][7][8][9][10], as well as with other parameters such as bone loss [11,12], fractures [11,13,14] and bone turnover [14][15][16]. However, these studies have provided controversial and inconclusive results due to differences in sample size, ethnic background and age group [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…There have been numerous studies that have examined the association between differing gene alleles and bone mineral density (BMD), many focusing on osteoporosis [9][10][11][12][13][14]. Using a genetic marker for the vitamin D receptor (VDR) gene, we have previously found ethnic differences in the BMD of African-American and white women and children [15].…”
Section: Introductionmentioning
confidence: 99%
“…In 2009, Dunbar et al studied Turkish menopausal women and showed that individuals with aa genotype had a lower bone density and higher serum calcium level in comparison with those with AA genotype (23). On the other hand, in 2004 in a similar study on Turkish menopausal women with osteoporosis, it was found that individuals with TT, Tt, and tt genotypes (TaqI) had the highest bone density and lowest serum calcitonin level (24). In Greek menopausal women with osteoporosis, none of the polymorphisms of BsmI and TaqI had a significant relationship with bone density (BMD), osteoporosis, and bone fractures, while having a significant relationship with calcium absorption (25).…”
Section: Discussionmentioning
confidence: 99%